The impact of mobile-assisted swimming applications on intrinsic motivation and fear reduction in aquatic environments among students in the swimming course - Alkasasbeh, Walaa Jumah; Alawamleh, Thekra; Aloran, Hasan; Farash, Tamara; Orhan, Bekir Erhan (Frontiers in Sports and Active Living, 2024)
Introduction This study investigates the impact of mobile-assisted swimming applications on intrinsic motivation and fear reduction in aquatic environments among students enrolled in a swimming course. While technological tools are increasingly integrated into physical education settings, their effects on motivation and psychological barriers such as fear of water remain underexplored. Methods A total of 69 male and female students enrolled in the “Swimming Education and Training” course participated in the study. The Intrinsic Motivation Scale (IMS) and the Water Fear Assessment Questionnaire (WFAQ) were used to measure intrinsic motivation and water-related fear, respectively, before and after using a mobile-assisted swimming application. Data were analyzed to assess changes in motivation and fear, and potential relationships with demographic variables (gender, academic year, parental swimming experience, and university GPA) were explored. Results The study found no statistically significant differences in intrinsic motivation levels before and after the use of the mobile-assisted swimming application. However, a statistically significant reduction in water fear was observed following the intervention. No significant relationships were found between demographic factors and either motivation or fear reduction. Discussion The results suggest that while the mobile-assisted swimming application did not significantly impact intrinsic motivation, it was effective in reducing fear of water among students. This highlights the potential of mobile applications in addressing psychological barriers in aquatic environments, supporting skill acquisition, and enhancing the overall learning experience in swimming courses. The absence of demographic influences suggests that the application's benefits may be broadly applicable across different student groups.